2012
DOI: 10.4161/cc.20905
|View full text |Cite
|
Sign up to set email alerts
|

S-phase sensing of DNA-protein crosslinks triggers TopBP1-independent ATR activation and p53-mediated cell death by formaldehyde

Abstract: We examined genotoxic signaling and cell fate decisions in response to a potent DNA-protein crosslinker formaldehyde (FA). DNA-protein crosslinks (DPC) are poorly understood lesions produced by bifunctional carcinogens and several cancer drugs. FA-treated human cells showed a rapid activation of ATR kinase that preferentially targeted the p53 transcription factor at low doses and CHK1 kinase at more severe damage, producing bell-shaped and sublinear responses, respectively. CHK1 phosphorylation was transient, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 69 publications
4
44
0
Order By: Relevance
“…25,26 In the present work, it was observed that treatment of NB-4 and U937 cells with cordycepin leads to upregulation of p53 expression. As the p53-specific inhibitor PFT-a can partially inhibit cordycepin-induced caspase-3 and caspase-9 activation, we proposed that cordycepin-induced apoptosis in NB-4 and U937 cells is both p53-dependent and -independent.…”
Section: Discussionmentioning
confidence: 74%
“…25,26 In the present work, it was observed that treatment of NB-4 and U937 cells with cordycepin leads to upregulation of p53 expression. As the p53-specific inhibitor PFT-a can partially inhibit cordycepin-induced caspase-3 and caspase-9 activation, we proposed that cordycepin-induced apoptosis in NB-4 and U937 cells is both p53-dependent and -independent.…”
Section: Discussionmentioning
confidence: 74%
“…A549 and H460 are human lung epithelial cell lines that we have previously examined for repair of FA-induced DPC and cytotoxic mechanisms (Quievryn and Zhitkovich, 2000; Wong et al, 2012). Both cell lines contain wild-type transcriptional factor p53, which plays a major role in DNA damage-induced cell fate decisions, including those triggered by FA (Wong et al, 2012). Since some regulatory networks are altered in all transformed cell lines, signaling responses to FA were investigated in IMR90 normal human lung fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to their human relevance, low doses help minimize formation and confounding effects of secondary lesions that occur in cells treated with highly toxic concentrations of FA. For example, high FA doses have been found to suppress p53 activation, resulting in a bell-shaped dose response (Wong et al, 2012). The majority of our experiments were conducted with 50–150 μM FA, which covered the physiological range of 30–100 μM FA in human serum of unexposed individuals (IARC, 2006; NTP, 2010) and included a moderately higher dosage of FA occurring locally during inhalation exposures.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it also can decrease the expression of Bcl-2 protein which can maintain mitochondrial homeostasis and prevent mitochondrial release of Cyt C (Ola et al, 2011). The changes of MMP affect the cell signal transduction, cell cycle regulation and DNA replication, while Cell cycle checkpoint controls DNA replication and mitotic starting, in order that it can guarantee the completeness and correctness of chromosomes (Wong et al, 2012). Our results demonstrated that SOD activity in each formaldehyde group was found to be significantly decreased, while MDA content was increased.…”
Section: Discussionmentioning
confidence: 99%